2014
DOI: 10.1039/c4ra09370d
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic chip for monitoring Ca2+transport through a confluent layer of intestinal cells

Abstract: The absorption of dietary calcium through the intestinal barrier is essential for maintaining health in general and especially of the bone system. We propose a microfluidic model that studies free calcium (Ca 2+ ) transport through a confluent monolayer of Caco-2 cells. The latter were cultured on a porous membrane that was positioned in between a top and bottom microfluidic chamber. Fresh cell culture medium was continuously supplied into the device at a flow rate of 5 nL s À1 and the culture progress of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 20 publications
2
10
0
Order By: Relevance
“…After functionalization of the apical side of the PC membrane with Matrigel, Caco-2 cells were injected inside the apical section of the IOAC device and left to attach for 4 h. At this time point, the apical chamber was then perfused with DMEM cell culture media supplemented with FBS at a flow rate calculated to induce an averaged fluid shear stress of 0.02 dyn cm –2 . In agreement with previous studies, dense Caco-2 cell monolayers were obtained typically after 5 days of culture in these dynamic culture conditions. The cell monolayers on the PC membrane were prepared for imaging with confocal microscopy which confirmed that the IOAC model allows for the formation of cell monolayers that possess undulating 3D morphology as shown by F-actin mapping of the apical surface of cell monolayer.…”
Section: Resultssupporting
confidence: 92%
“…After functionalization of the apical side of the PC membrane with Matrigel, Caco-2 cells were injected inside the apical section of the IOAC device and left to attach for 4 h. At this time point, the apical chamber was then perfused with DMEM cell culture media supplemented with FBS at a flow rate calculated to induce an averaged fluid shear stress of 0.02 dyn cm –2 . In agreement with previous studies, dense Caco-2 cell monolayers were obtained typically after 5 days of culture in these dynamic culture conditions. The cell monolayers on the PC membrane were prepared for imaging with confocal microscopy which confirmed that the IOAC model allows for the formation of cell monolayers that possess undulating 3D morphology as shown by F-actin mapping of the apical surface of cell monolayer.…”
Section: Resultssupporting
confidence: 92%
“…(2) Model C has one pair of current carrying and pick-up electrodes at the surfaces of both chambers but in opposite sides. Despite the fact that the electrodes are planar and placed on the chamber surface, results are similar to those expected for models where wire electrodes are located at specific positions of the chamber [6,41].…”
Section: Simulation Modelsupporting
confidence: 74%
“…When integrated into microfluidic organ-on-a-chip devices, impedance measuring electrodes allow long-term monitoring of the cultured cells in a controlled environment (Douville et al, 2010;Booth and Kim, 2012;Griep et al, 2013;Huang et al, 2014;Walter et al, 2016). The size constraint, which is common with respect to microfluidic platforms, dictates the placement of electrodes in close proximity to the cells.…”
Section: Investigations Of Barrier Functionsmentioning
confidence: 99%